Luaran Klinis dan Tantangan Teknis Total Hip Replacement pada Pasien Muda dengan Dislokasi Panggul yang Terabaikan - Sadi, Fadilla N. R.; Kambey, Stefan A. G. P.; Wagiu, Angelica M. J. (Universitas Sam Ratulangi, 2026)
Abstract: Neglected hip dislocation in young patients often leads to severe deformity, soft-tissue contractures, avascular necrosis, and secondary osteoarthritis. Total hip replacement (THR) has become a viable reconstructive option, although the available evidence remains limited and is primarily derived from small case series. This study aimed to evaluate the clinical and functional outcomes of THR in young patients with neglected hip dislocation. A structured search was conducted across six predetermined databases for studies published between 2015 and 2025, following PRISMA and PICOS guidelines. 18 studies met the inclusion criteria and were appraised using the OCEBM 2011 and JBI 2020 tools. Most studies reported substantial postoperative improvement, including marked pain reduction and significant increases in functional scores—particularly the Harris Hip Score, with average gains of 40–50 points. Major complications were uncommon, and uncemented THR was more frequently employed to preserve bone stock. The main surgical challenges included acetabular deformity, soft-tissue fibrosis, limb-length discrepancy, and risk of recurrent dislocation. In conclusion, THR appears effective in restoring function and improving quality of life in young patients with neglected hip dislocation, although larger prospective studies are required to strengthen the long-term evidence base. Keywords: total hip replacement; neglected hip dislocation; young patients Abstrak: Dislokasi panggul terabaikan pada pasien muda sering menyebabkan deformitas berat, kontraktur jaringan lunak, avaskular nekrosis, dan osteoartritis sekunder. Total hip replacement (THR) telah menjadi pilihan rekonstruksi yang layak, meskipun bukti yang ada masih terbatas dan terutama berasal dari seri kasus kecil. Penelitian ini bertujuan untuk menilai luaran klinis dan fungsional dari THR pada pasien muda dengan dislokasi panggul terabaikan. Pencarian terstruktur dilakukan pada enam basis data yang telah ditentukan untuk studi yang dipublikasikan antara tahun 2015 hingga 2025, mengikuti pedoman PRISMA dan PICOS. Terdapat 18 studi memenuhi kriteria inklusi dan dinilai menggunakan alat penilaian OCEBM 2011 dan JBI 2020. Sebagian besar studi melaporkan perbaikan pascaoperasi yang substansial, termasuk penurunan nyeri yang jelas dan peningkatan bermakna pada skor fungsional—terutama Harris Hip Score, dengan kenaikan rerata 40–50 poin. Komplikasi mayor jarang terjadi, dan THR uncemented lebih sering digunakan untuk mempertahankan cadangan tulang. Tantangan bedah utama mencakup deformitas asetabulum, fibrosis jaringan lunak, ketidaksamaan panjang tungkai, dan risiko dislokasi ulang. Simpulan penelitian ini ialah THR tampak efektif dalam memulihkan fungsi dan meningkatkan kualitas hidup pada pasien muda dengan dislokasi panggul terabaikan, meskipun studi prospektif yang lebih besar diperlukan untuk memperkuat bukti jangka panjang. Kata kunci: total hip replacement; dislokasi panggul terabaikan; pasien muda